The Effect of Outpatient Service Quality on Patient Satisfaction at Kalidoni Health Center, Palembang City - Nifi Lamingthon; Rusdi Laili; Reni Juliati (GAYAKU PUBLISHER, 2022)
As a general public health service, Puskesmas has a major problem, namely whether the services provided are in line with patient expectations or not. Therefore, the puskesmas is required to always maintain patient trust by improving the quality of their services. Quality health services are health services that can satisfy every user of health health services in accordance with the level of satisfaction of the average population and whose implementation is in accordance with established standards and professional codes of ethics. The research method used is a quantitative method. Data was collected by means of observation, questionnaires, literature study. Data analysis was carried out by means of a simple regression test. The results of the research and discussion showed that the quality of services at the Kalidoni Health Center, Kalidoni District, Palembang City received an assessment of 88.36% of the expected value (expected value of 100%). This means that it can be assumed that the Kalidoni Health Center, Kalidoni District, Palembang City has been able to provide quality services to the community. This is due to complete infrastructure and good human resources. Patient Satisfaction at Kalidoni Public Health Center, Kalidoni District, South Palembang City received a very good rating (with a score of 88.75). The officer has given a good explanation of service procedures, discipline in work, is responsible for work, provides a safe and comfortable place, and service rates do not deviate from regulations, Service Quality has an effect on Patient Satisfaction, the value obtained states that there is a positive influence and between public service and satisfaction (76.5%). The results obtained indicate that if the service is improved, then patient satisfaction will also increase. The positive influence was obtained because of the willingness of officers to provide services and being able to control themselves. So that in serving the community, officers are able to maximize all the elements in the theory of service quality.